2007
DOI: 10.1111/j.1525-1438.2007.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis from cervical carcinoma

Abstract: The aim of this study was to describe the features of patients with brain metastasis from cervical cancer. Twelve patients with brain metastasis from cervical cancer were identified. Information regarding symptoms, treatment, and survival was analyzed. The incidence of brain metastasis in our population was 0.77%. Median patient age at initial diagnosis of cervical cancer was 43.5 years (range 29-57 years) compared with 44.5 years (range 31-58 years) at identification of brain metastasis. Six patients had FIGO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(106 citation statements)
references
References 24 publications
4
91
0
11
Order By: Relevance
“…Ikeda et al (7) reported that the initial stage was IIB in four of eight patients with brain metastasis from uterine cervical cancer. In a series of twelve cases from Chura et al (3), nine patients were stage IIB or below, while three patients were higher than stage IIB. In our study, four cases had an initial stage higher than IIB and eleven patients were stage IIB or below.…”
Section: █ Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Ikeda et al (7) reported that the initial stage was IIB in four of eight patients with brain metastasis from uterine cervical cancer. In a series of twelve cases from Chura et al (3), nine patients were stage IIB or below, while three patients were higher than stage IIB. In our study, four cases had an initial stage higher than IIB and eleven patients were stage IIB or below.…”
Section: █ Discussionmentioning
confidence: 94%
“…However, it is a rare development in uterine cervical cancer, with an incidence rate of only 0.4% to 1.2% (3,4,7,16). Recently, brain metastasis has been seen more frequently.…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (20,21). On the other hand, uterine cervical cancer with brain metastasis is rare with an incidence of 0.44-1.18% (22)(23)(24), and there are no reports of intra-cavernous metastasis. Here, we describe a case presenting with this combination symptoms as an initial manifestation of uterine cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal metastases from primary SqCC cervix are rarely reported in literature [4] while brain metastases are extremely rare [1,5,6] with an incidence of 0.4%-1.2% [7][8][9][10]. Similarly, SqCC of vagina most commonly metastasizes to lung, bone and least commonly to liver while adrenal and brain metastases are rarely heard of [11].…”
Section: Introductionmentioning
confidence: 99%